Progress in the application of motor imagery therapy in upper limb motor function rehabilitation of stroke patients with hemiplegia - Shen, Shuying; Chu, Tianchen; Wang, Jing; Zhao, Hangyu; Tang, Jinli; Xu, Linya; Ni, Wei; Tan, Liping; Chen, Yu (Frontiers in Neurology, 2025)
Stroke is the leading cause of disability in Chinese adults. Upper limb motor dysfunction is a common manifestation of neurological dysfunction after stroke and can exert significant effects on a patient’s daily living ability and quality-of-life. Therefore, it is crucial to provide appropriate rehabilitation treatment for upper limb motor function in stroke patients with hemiplegia. Currently, rehabilitation treatment for upper limb motor function in hemiplegic stroke patients in China includes motor therapy, neuro-promoting technology, occupational therapy, physical factor intervention, speech therapy, and swallowing therapy. Motor imagery therapy has also been shown to effectively promote the rehabilitation of upper limb function in stroke patients. Here, we review the concept, classification, mechanism of action, application, and effect of motor imagery therapy for the rehabilitation of upper limb motor function in stroke patients with hemiplegia in China. We summarize the available evidence, arising from Chinese experience, to support the implementation of this method in medical and rehabilitation institutions.